2022
DOI: 10.1136/archdischild-2021-323630
|View full text |Cite
|
Sign up to set email alerts
|

National rates and disparities in childhood vaccination and vaccine-preventable disease during the COVID-19 pandemic: English sentinel network retrospective database study

Abstract: ObjectivesTo describe rates and variation in uptake of pneumococcal and measles, mumps and rubella (MMR) vaccines in children and associated change in vaccine-preventable diseases (VPDs) across the first and second waves of the COVID-19 pandemic.MethodsRetrospective database study of all children aged <19 registered with a general practice in the Oxford Royal College of General Practitioners Research and Surveillance Centre English national sentinel surveillance network between 2 November 2015 and 18 July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
(40 reference statements)
2
8
0
Order By: Relevance
“…However, there is heterogeneity within these results according to geographical area of interest 31. We found that children from black and mixed/other ethnic backgrounds were less likely to receive timely vaccination, broadly consistent with findings from studies of COVID-19 vaccination uptake which have shown lowest uptake among people from black ethnic backgrounds 32 33. Additional qualitative evidence suggests women from minority ethnic backgrounds were more likely to find it difficult to access and felt less safe accessing vaccinations for their babies during the COVID-19 pandemic 34…”
Section: Discussionsupporting
confidence: 81%
“…However, there is heterogeneity within these results according to geographical area of interest 31. We found that children from black and mixed/other ethnic backgrounds were less likely to receive timely vaccination, broadly consistent with findings from studies of COVID-19 vaccination uptake which have shown lowest uptake among people from black ethnic backgrounds 32 33. Additional qualitative evidence suggests women from minority ethnic backgrounds were more likely to find it difficult to access and felt less safe accessing vaccinations for their babies during the COVID-19 pandemic 34…”
Section: Discussionsupporting
confidence: 81%
“…uptake of the MMR vaccine in England [2]. The need for this strategic focus accords with our estimates, which further identify widening disparities in childhood vaccine uptake [3].…”
supporting
confidence: 55%
“…Coverage of the second dose of MMR decreased from 85.0% (95% CI 84.7% to 85.3%) at its height in September 2020 to 84.1% (95% CI 83.8% to 84.4%) by July 2021. Importantly, decreases in vaccine coverage varied by ethnicity, socioeconomic status and population density with a greater decline in non-white ethnicities, the most deprived socio-economic groups and in conurbations [3].…”
mentioning
confidence: 99%
“…The WHO reported in May 2020 that 68 lower income countries had reduced or suspended immunisation programmes, while in the United Kingdom the immunisation rate for measles, mumps and rubella decreased by 20% at one point, although rates have recovered since. 42 , 43 Coverage of UK children with PCV13 fell from 94.5% in 2020 to 93.6% in July 2021. Measles, mumps and rubella immunisation coverage fell from 85.0% to 84.1% over the same period.…”
Section: Effect Of Covid-19 On ‘Normal Infection Rate’mentioning
confidence: 99%